Normalized solutions for fractional Schrodinger-Choquard systems with Sobolev critical coupled nonlinearity - Zilin Chen; Yang Yang (Electronic Journal of Differential Equations)
We study the existence of normalized solutions for a system of fractional Schrodinger-Choquard with Sobolev critical coupling term. We obtain the existence of the positive normalized ground state solution, and in a special case we obtain a mountain pass type normalized solution.